2020
DOI: 10.1186/s12974-020-01789-2
|View full text |Cite
|
Sign up to set email alerts
|

Independent and inter-dependent immunoregulatory effects of NCF1 and NOS2 in experimental autoimmune encephalomyelitis

Abstract: Background: Increasing evidence has suggested that a single nucleotide polymorphism in the Ncf1 gene is associated with experimental autoimmune encephalomyelitis (EAE). However, the mechanisms of NCF1-induced immunoregulatory effects remain poorly understood. In this study, we focus on NCF1 deficiency-mediated effects on EAE in NOS2 dependent and independent ways. Methods: To determine the effects of NCF1 and NOS2 during EAE development, we have established recombinant mouse strains deficient at NCF1 and/or NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Previously, we and others have found a role of ROS in the regulation of IL-1β expression 12 , 23 . In this study, we show that ROS-sufficient neutrophils express an enhanced IL-1β in conditional knock-in mice (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Previously, we and others have found a role of ROS in the regulation of IL-1β expression 12 , 23 . In this study, we show that ROS-sufficient neutrophils express an enhanced IL-1β in conditional knock-in mice (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…It should be pointed out that the small compound histamine dihydrochloride might not specifically affect NK cells, and there is also genetic difference between the knockout mouse strains and naturally mutant strains. For an example, both Nox2 -knockout mice and Ncf1 -knockout mice have been reported to be protected from experimental autoimmune encephalomyelitis 44 , but the Ncf1 mutant mice exhibited an enhanced autoimmune encephalomyelitis 12 , 45 . Therefore, we further studied the role of NK cells in the Ncf1 mutant mice using anti-NK1.1 antibody 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the susceptible Qa2 nul mice of B6R strain, we found that the Ncf1 mutation led to both ear and nail psoriasis. These results suggest that the Ncf1 mutation has an essential role in psoriasis spread, of which downstream pathways could be elicted by proinflammatory Ly6C monocytes to activate the local γδ T cells (Zhong et al 2020a;Zhong et al 2018b).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 92%
“…We have previously found that a natural mutation in the Ncf1 gene impairs the formation of the NADPH oxidase 2 (NOX2) complex and the generation of reactive oxygen species (ROS) [ 1 , 12 ], promotes the proliferation of autoreactive CD4 T cells in spontaneous arthritis [ 13 , 14 ], enhances autoimmune encephalomyelitis in the absence of inducible nitric oxide [ 15 ], promotes the spread of psoriasis through innate production of interleukin 17 (IL-17) [ 16 , 17 , 18 ], activates STAT1 signaling in exaggerated lupus [ 19 ], and suppresses NETosis in neutrophils prepared from patients with the chronic granulomatous disease and autoimmune disorders [ 3 , 20 ]. 147-base pair of NET DNA is typically packed around a histone octamer composed of two copies of each of the histones H3, H4, H2A, and H2B [ 21 ].…”
Section: Introductionmentioning
confidence: 99%